Child Marriage in Villages: Misuse of Ijbār, Structural Discrimination, and Best Interest of the Child Dismissal - Rifqi, Muhammad Jazil; Masdar Hilmy; Moh. Faizur Rohman; M Imdadur Rohman (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2025)
Despite ongoing global efforts to end child marriage, the practice remains widespread in Indonesia. In 2024, Pasuruan recorded some of the highest child marriage rates. Ngantungan Village in Pasrepan is a striking example of how entrenched cultural beliefs and economic pressures continue to drive the trend. This study investigates how structural discrimination—primarily through the practice of ijbār (coercive guardianship) in Islamic legal interpretation—clashes with the best interests of the child (BIC) and perpetuates early marriage. Fieldwork included interviews with religious authorities, local officials, guardians, and young people involved in these marriages. The findings reveal that although Islamic jurisprudence allows guardians to arrange underage marriages under certain conditions, ijbār is frequently misapplied in ways that ignore girls' autonomy and strip them of their right to participate in life-changing decisions. In Ngantungan, traditional myths—like the belief that rejecting too many proposals dooms a girl to lifelong singleness—create social pressure, particularly for girls from low-income families with little formal education. For many, early marriage is seen not as a choice but as the only viable escape from economic hardship. Tackling this issue calls for more than legal reform. It demands a cultural shift, localized education initiatives, and financial support programs that offer meaningful alternatives and disrupt the cycle of child marriage.